Sales and operations planning (S&OP): bringing it all together - Moon, Mark (Henry Stewart Talks, 2010)
What is Demand/Supply Integration (DSI), How is DSI Different from S&OP?, The Ideal State of DSI, Collaboration Across the Supply Chain, Unconstrained Demand, Typical DSI Aberrations, Characteristics of Successful DSI Implementations, Senior Management Accountability, The Levers of Change Management, Overcoming Cultural Differences